KESEMPATAN MEMPEROLEH PENDIDIKAN PADA MASYARAKAT PESISIR PONJALAE, PALOPO: SEBUAH ANALISIS PERSPEKTIF GENDER - Irayanti Nur; Chece Djaffar (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2020)
Gender equality is a situation for women and men to take the same status, in order to fully realize their human right. It has the same potential both men and women regarding to the all aspects in their life, including for fisherwomen. This study aims to (1) describe the social culture of the coastal communities of Ponjalae where the fisherwomen lives and (2) identify gender equality and the role of women to get education opportunity. This is a case study research where the informants are the fisherwomen in the coastal communities of Ponjalae, Palopo. Interactive data analysis are performed in this research. Findings indicate that fisherwomen and their children have restricted access to get education related to economic difficulties. In line withthe previousfinding, there is a misleading social stigma to the proper position of women at home. Based on the results of this study, it could recommend for government through their policies which could improve the opportunity for getting an education, especially forfisherwomen to promote gender equality.